5G mobile challenges: A feasibility study on achieving carbon neutrality - Gonçalves, L. C. (2021)
Increasingly mobile data traffic and high quality service demand has driven fast standards development and new mobile technologies deployment. Traffic demand in 5G networks is expected to rise unprecedentedly, bringing mobile network operators (MNOs) additional challenges, and added pressure regarding carbon footprint reduction. This work aims to study the environmental and financial feasibility of MNOs becoming carbon neutral, by developing biotic carbon dioxide sequestration programs. If feasibility exists, it would be extended and applied to future networks and other environmental scenarios. It is shown that achieving carbon neutrality is possible for heterogeneous deployments, especially when low energy powered base stations like femtocells exist and that the financial costs of such aim might represent little or negligible additional cost expenditure, with the added value of greener and environmental friendly network operation.